Der Generalstabschef der französische Luftwaffe eingetroffen. Milch begrüsst Vuillemin (an die linke Seite)
Der Generalstabschef der französische Luftwaffe eingetroffen. Milch begrüsst Vuillemin (an die linke Seite).